FORMATION OF TITANIUM-CONTAINING PHOSPHATES IN POLYPHOSPHATE ACIDS' MELTS: UDC 546.185 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Phase relationships in the polyphosphate acids- containing melted systems of Ti–P2O5–Н2O, Ti2O3–P2O5–Н2O, TiN–P2O5–Н2O andwith presents of alkali oxides (lithium, sodium and potassium) were investigated. Conditions of Ti(PO3)3 and TiP2O7 crystallization wereidentified. High stability of Ti (III) in melts of polyphosphate acids for temperature range of 350–600 °С was shown. Suitable pathway ofTi(PO3)3 preparation was proposed. UV/VIS, FTIR and EPR spectra of titanium (III) metaphosphate were discussed. The scheme of thermal decomposition of latter compound was determined on the basis of DTA data
Keywords: -